Kajian Penggunaan Finishing Material Ruang Observasi Pasien Skizofrenia Berdasarkan Aspek Keamanan (Studi Kasus : Ruang Observasi Bali Mental Health Clinic, Bali) - Khurina Nuril Firdausy; Heru Prasetiyo Utomo (Universitas Medan Area, 2026)
In patients with schizophrenia, hallucinations can trigger emotional dysregulation such as uncontrollable anger, potentially leading to violent behavior. This is often triggered by hallucinations of voices that are perceived to be mocking, although not real. Such anger can be harmful to oneself and the environment. Research shows that construction materials affect psychological well-being through sensory stimulation, which can exacerbate or relieve stress. This qualitative research uses a case study of the observation room at Bali Mental Health Clinic, focusing on whether the selection of finishing materials is in accordance with the Ministry of Health's inpatient facilities standards. The analysis was conducted through field observations and literature studies. The study results show that the materials used are mostly in accordance with health standards. The researcher recommends the use of safer materials to improve the safety of the observation room for patients.